THE KYRGYZ REPUBLIC BUDGET - A. O. Kozhoshev (Финансы: теория и практика)
The article analyzes the main indicators of the GDP and the republican budget of the Kyrgyz Republic over the last 25 years. It proves that there is a direct link between the budget, living standards and the rational use of national wealth. The listed statistical data show that drastic measures should be taken to change the social and economic situation in the republic. One of the main conditions for further development is the availability of accurate information about the national wealth of the republic. Therefore, to determine further actions, it is necessary, in the first place, to make an inventory, identification, registration and re-evaluation of the national wealth. Moreover, it is needed to carry out deeper reforms of the budget process, to improve financial and fiscal relations in order to optimize budget expenditures with the aim to reach goals set by the government.